Bacterial toxins: Offensive, defensive, or something else altogether? - Justine K Rudkin; Rachel M McLoughlin; Andrew Preston; Ruth C Massey (PLoS Pathogens, 2017)
The secretion of proteins that damage host tissue is well established as integral to the infectious processes of many bacterial pathogens. However, recent advances in our understanding of the activity of toxins suggest that the attributes we have assigned to them from early in vitro experimentation have misled us into thinking of them as merely destructive tools. Here, we will discuss the multifarious ways in which toxins contribute to the lifestyle of bacteria and, by considering their activity from an evolutionary perspective, demonstrate how this extends far beyond their ability to destroy host tissue.